A Review of the Psychometric Properties and Use of the Rheumatoid Arthritis Quality of Life Questionnaire (RAQoL) in Clinical Research - Heaney, Alice; Stepanous, Jessica; Rouse, Matthew; McKenna, Stephen P (Current Rheumatology Reviews, 2017)
Background: Several Patient-Reported Outcome Measures (PROMs) have been used in studies of Rheumatoid Arthritis (RA). Most of these assess Health-Related Quality of Life (HRQL). The exception is the Rheumatoid Arthritis Quality of Life questionnaire (RAQoL). This scale measures the impact of RA and its treatment from the patient's perspective, making it suitable for determining the value patients gain from interventions. Objective: This review collates literature reporting on the efficacy of the RAQoL as a measure of patient value in clinical studies. Method: A literature search was conducted to identify published articles reporting on the use of the RAQoL. Psychometric and clinical research studies were included in the review. Results: Sixty-three full articles were identified. Psychometric analyses demonstrated that the RAQoL meets the requirements for internal consistency, reproducibility and construct validity. There is evidence to support the unidimensionality and responsiveness of the RAQoL. The measure has been used in a wide range of research studies including interventional, correlational and nonexperimental studies. Several studies found the RAQoL to be sensitive to change following interventions. Conclusion: The RAQoL has excellent psychometric properties and can detect the impact of both clinical and non-clinical interventions. As a patient-centric measure of patient value, the RAQoL will also prove valuable in big data analytics and for use in outcomes-based reimbursement (OBR).
Keywords: RAQoL